Future Internet Protocols - Petrie, Charles; Spatscheck, Oliver (IEEE internet computing, 2012)
The Internet is based on a layered set of protocols — the most basic of which is TCP/IP — and the servers and routers that support them. This special issue addresses challenges to the Internet's basic protocols as our collective Internet usage increases in both magnitude and type and becomes increasingly crucial for our economy and culture. "Designing a Deployable Internet: The Locator/Identifier Separation Protocol" shows how to achieve better scalability for mobile devices by separating the location from the identification function of the IP addresses. "IPv6 Deployment and Spam Challenges" shows that IPv6 introduces new problems for fighting spam and denial-of-service attacks, and offers solutions. "All-Weather Transport Essentials" surveys current Internet protocols and principles for their revision to address known problems that can be expected to become more serious in the near future.